Human Milk Mucin 1 and Mucin 4 Inhibit Salmonella enterica Serovar Typhimurium Invasion of Human Intestinal Epithelial Cells In Vitro(2) - Liu, Bo (American Society for Nutrition, 2012)
Many human milk glycans inhibit pathogen binding to host receptors and their consumption by infants is associated with reduced risk of disease. Salmonella infection is more frequent among infants than among the general population, but the incidence is lower in breast-fed babies, suggesting that human milk could contain components that inhibit Salmonella. This study aimed to test whether human milk per se inhibits Salmonella invasion of human intestinal epithelial cells in vitro and, if so, to identify the milk components responsible for inhibition. Salmonella enterica serovar Typhimurium SL1344 (SL1344) invasion of FHs 74 Int and Caco-2 cells were the models of human intestinal epithelium infection. Internalization of fluorescein-5-isothiocyanate–labeled SL1344 into intestinal cells was measured by flow cytometry to quantify infection. Human milk and its fractions inhibited infection; the inhibitory activity localized to the high molecular weight glycans. Mucin 1 and mucin 4 were isolated to homogeneity. At 150 μg/L, a typical concentration in milk, human milk mucin 1 and mucin 4 inhibited SL1344 invasion of both target cell types. These mucins inhibited SL1344 invasion of epithelial cells in a dose-dependent manner. Thus, mucins may prove useful as a basis for developing novel oral prophylactic and therapeutic agents that inhibit infant diseases caused by Salmonella and related pathogens.